PERANAN KELOMPOK WANITA TANI DALAM MENINGKATKAN POTENSI UMKM MASYARAKAT DI DESA ADIREJO - Vera Ismail; Rusy Dina Firjanah; Ariq Cindra Kurniawan; Millatul Azza; Atika Wibi Audrey; Lutfi Nur Laila (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
The creative economy is the innovative ideas, skills, and talents individuals possess. The creative economy can provide prosperity and open up employment opportunities through digital marketing technology. Micro, Small and Medium Enterprises (MSMEs) can utilize digital technology as a promotional medium or what can be called digital marketing. The average community does not use digital technology as a promotional medium, and sales of MSME products are not optimal. This problem also occurred in one of the Haruma Jaya Farming Women's Groups (KWT) in Adirejo Dusun IV village which developed knitted bag products, beads, etcetra. KWT members said that old age hinders knowledge about digital promotional media. Based on these problems, socialization activities on the role of the Women's Farmer Group and training on creating a TikTok Shop were carried out to increase the potential of MSMEs in Adirejo village. The implementation of this service activity consists of several stages of methods used, including socialization, training, mentoring and evaluation. The result of this activity is the increased understanding of the Women Farmers Group (KWT) regarding digital technology which can have potential for MSMEs in Adirejo village with the Tiktok Shop.